ANALISIS KEMAMPUAN NUMERASI PESERTA DIDIK DALAM PENYELESAIAN SOAL MATEMATIKA PADA MATERI OPERASI HITUNG PECAHAN KELAS V SD NEGERI KEBONDALEM - Khoirudin, Maftukh; Anjani, Titi; Suyoto, Suyoto (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
Education is an effort to change individual behaviour through learning to become a better person. The education system in elementary school currently uses the AKM which contains numeracy literacy skills. Numerical literacy is the ability to think to solve mathematical problems related to everyday life using concepts, procedures, facts, and tools. The problem that often arises is the problem of fractions. This study aims to describe the numeracy skills of students in solving math problems in fractional operations material for the fifth-grade student of SD Negeri Kebondalem. The method used is descriptive qualitative. Data collection using tests and interviews. Data analysis techniques using Miles & Huberman's model include data reduction, data presentation, and conclusions/verification. The results of this study stated the numeracy skills of fifth-grade students of SD Negeri Kebondalem were categorized as low. The results of the numeracy abilities of the fifth-grade students of SD Negeri Kebondalem are low because in terms of aspects: (a) Interpreting the results of the analysis, it was found only 1 subject got a good score while the rest got low scores, (b) Counting skills and the use of various types of numbers and symbols, the result is only 1 subject gets a score, and (c) ability to use charts, graphs, tables, and diagrams, the result is all subjects do not get a score.